Pola Pengasuhan dalam Keluarga dan Dampaknya terhadap Prestasi Akademik Mahasiswa - Sene, Mikael; Loy, Paskalis Kristianus; Kelen, Marta Rosyanti (Ideas Publishing, 2024)
The background to this research is that there is a difference in the cumulative achievement index between students and female students in the UNIKA Weetebula Catholic Religious Education Study Program, where the average GPA of female students is better than that of female students. The aim of this research is to determine the impact of parenting patterns and division of roles in the family based on James Coleman's perspective on children's academic achievement. This research is a qualitative descriptive research. The research results show that the human resource capital (HR), financial/economic capital and social capital of parents are quite low. The pattern of gender-based division of labor in the family has an impact on character formation in learning and learning outcomes.